Effects of different intensities of continuous training on vascular inflammation and oxidative stress in spontaneously hypertensive rats. Issue 17 (31st July 2021) - Luo, Minghao; Cao, Chunmei; Niebauer, Josef; Yan, Jianghong; Ma, Xindong; Chang, Qing; Zhang, Ting; Huang, Xiaoxiao; Liu, Guochun
Abstract: We aimed to study the effects and underlying mechanism of different intensities of continuous training (CT) on vascular inflammation and oxidative stress in spontaneously hypertensive rats (SHR). Rats were divided into five groups ( n = 12): Wistar‐Kyoto rats sedentary group (WKY‐S), sedentary group (SHR‐S), low‐intensity CT group (SHR‐L), medium‐intensity CT group (SHR‐M) and high‐intensity CT group (SHR‐H). Changes in body mass, heart rate and blood pressure were recorded. The rats were euthanized after 14 weeks, and blood and vascular tissue samples were collected. Haematoxylin and Eosin staining was used to observe the aortic morphology, and Western blot was used to detect the expression of mesenteric artery proteins. After CT, the mean arterial pressures improved in SHR‐L and SHR‐M and increased in SHR‐H compared with those in SHR‐S. Vascular inflammation and oxidative stress levels significantly subsided in SHR‐L and SHR‐M ( p < 0.05), whereas in SHR‐H, only vascular inflammation significantly subsided ( p < 0.05), and oxidative stress remained unchanged ( p > 0.05). AMPK and SIRT1/3 expressions in SHR‐L and SHR‐M were significantly up‐regulated than those in SHR‐S ( p < 0.05). These results indicated that low‐ and medium‐intensity CT can effectively reduce the inflammatory response and oxidative stress of SHR vascular tissue, and high‐intensity CT can improve vascular tissue inflammation but not oxidative stress.